2023
DOI: 10.1108/jfbm-06-2023-0087
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the use of technologies and digitalization strategies for digital transformation in family businesses

Sérgio Begnini,
Ieda Margarete Oro,
Graciele Tonial
et al.

Abstract: PurposeAnalyzing the effect of digitalization strategies and barriers to digital transformation (DT) on the use of technologies, in the Brazilian context, is necessary to broaden the understanding of topics in emerging economies. Thus, empirical research to evaluate and analyze aspects related to DT in small and medium-sized family businesses in an emerging economy is necessary, as it is a necessary strategic alternative in the current context.Design/methodology/approachUsing data from a survey conducted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Current research on DS primarily focuses on its antecedents and impacts. For example, a DS has been found to positively influence firms' economic [41][42][43], innovative [37], and social performance [44]; Begnini et al (2023) [45] demonstrated that a DS positively affects the use of technology; Nguyen et al (2024) [35] identified three stakeholder factors (customer orientation, supplier collaboration, and employees' IT skills) that positively contribute to fostering a big data organizational culture, thereby facilitating DS implementation; and Low and Bu (2021) [46] argued that internal corporate social responsibility (CSR) practices positively impact employees' organizational commitment, while a DS mediates the relationship between internal CSR practices and affective commitment.…”
Section: Digitalization Strategymentioning
confidence: 99%
“…Current research on DS primarily focuses on its antecedents and impacts. For example, a DS has been found to positively influence firms' economic [41][42][43], innovative [37], and social performance [44]; Begnini et al (2023) [45] demonstrated that a DS positively affects the use of technology; Nguyen et al (2024) [35] identified three stakeholder factors (customer orientation, supplier collaboration, and employees' IT skills) that positively contribute to fostering a big data organizational culture, thereby facilitating DS implementation; and Low and Bu (2021) [46] argued that internal corporate social responsibility (CSR) practices positively impact employees' organizational commitment, while a DS mediates the relationship between internal CSR practices and affective commitment.…”
Section: Digitalization Strategymentioning
confidence: 99%